Métissages et espaces transculturels : reflet d’image et mises en scène chez les Indiens Tapeba - Martin Soares (Cahiers des Amériques Latines, 2010)
The Indian tapeba, following the example of most of the native groups of the Brazilian Nordeste, invent and stage their cultural heritage to fight against the absence of an history erased by a colonial context which did not authorize the political recognition of their ethnic peculiarity. The construction of a museum and a cultural center in the heart of their territory in suburb of the capital of Ceará has for objective to compensate for this lack of anteriority by trying to testify of an alive memory susceptible to feign an historic continuity by the transmission which she supposes. The globalization, the world tourism and the international distributions of the image become then precious instruments to lend a visibility to the group tapeba, so by going beyond the borders of Brazil and by bringing to the invention of their everyday life a transcultural dimension.